2003
DOI: 10.1103/physreve.68.036404
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of ion-wave wakefield by the resonant absorption of a short pulsed microwave with plasma

Abstract: Unmagnetized, inhomogeneous laboratory plasma irradiated by a high power (eta=E(2)(0)/4pin(e)kT(e) approximately 5.0x10(-2)) short pulsed microwave with pulse length of the order of ion-plasma period (tau(pi) less, similar 2pi/omega(pi)) is studied. Large density perturbation traveling through the underdense plasma with a velocity much greater than the ion sound speed produced by the resonant absorption of the microwave pulse has been observed. In the beginning the density perturbation has large amplitude (del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…3,5,11 Another physical phenomenon to eject particles from the resonance region is that when the resonant electric field goes to a sufficiently high level, the associated ponderomotive force pushes the trapped electrons in the wave toward the outside and, as a consequence, these suprathermal electrons can pull the ions from the critical density layer by the ambipolar Coulomb force and drive a suprathermal ion bunch. 10,17,[19][20][21] In the present experiment, it is also observed that a self-consistent ambipolar force pulls out the ion bunch from the resonance region and this ion bunch can travel through the underdense plasma. The energy of this accelerated ion bunch is observed տ10 kT e .…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…3,5,11 Another physical phenomenon to eject particles from the resonance region is that when the resonant electric field goes to a sufficiently high level, the associated ponderomotive force pushes the trapped electrons in the wave toward the outside and, as a consequence, these suprathermal electrons can pull the ions from the critical density layer by the ambipolar Coulomb force and drive a suprathermal ion bunch. 10,17,[19][20][21] In the present experiment, it is also observed that a self-consistent ambipolar force pulls out the ion bunch from the resonance region and this ion bunch can travel through the underdense plasma. The energy of this accelerated ion bunch is observed տ10 kT e .…”
Section: Introductionsupporting
confidence: 67%
“…The ponderomotive force expels electrons from the resonance region, resulting in leaving a bunch of ions around the neighborhood of the critical surface layer, and finally this bunch of ions can be accelerated by the created ambipolar Coulomb force from the resonant layer. 10,17,[19][20][21]23 One can observe in the typical oscillogram shown in Fig. 4 that the resonant absorption of a short microwave pulse produces a bunch of accelerated ions.…”
Section: Resultsmentioning
confidence: 92%
“…It propagates along the density gradient into the region of low plasma density with a characteristic velocity of (3-5) c s and can be interpreted as a bunch of accelerated charged particles formed due to the plasma drive-out from the resonance region by the striction pressure of the plasma-wave field on electrons. Such bunches of suprathermal particles, as well as the nonlinear ion-acoustic waves, are most efficiently formed if the characteristic duration of the microwave pulse is about π/ω pi [6,9,20,10].…”
Section: Ion Acceleration Upon Resonant Absorption Of a Microwave Pulmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Some of the observed consequences are generation of high-energy electron bunches, 1,2 excitation of temporal plasma-wave echoes in the ion wave regime, 3 excitation of ion-wave wakefield, 4 large amplitude electron plasma waves (EPW) based plasma accelerators, 5,6 and self-generation of magnetic fields. 7 The propagation of electromagnetic (em) waves through temporally growing plasmas has also been analyzed, mainly in theory, [8][9][10] including the study of dynamic behavior of microwaves through a gaseous medium that get ionized in the incident wave field.…”
Section: Introductionmentioning
confidence: 99%